NEAT1: Culprit lncRNA linking PIG-C, MSLN, and CD80 in triple-negative breast cancer - Hussein, Nada H.; Eissa, Reda A.; de Bruyn, M.; El Tayebi, Hend.M. (Life sciences (1973), 2022)
Breast cancer (BC) is the most common cancer in women. Despite the effectiveness of conventional therapies, they cause detrimental side effects. Glycosyl-Phosphatidyl-Inositol (GPI) pathway is a conserved pathway that culminates in the generation of GPI anchored proteins (GPI-AP). Phosphatidyl-Inositol-Glycan Biosynthesis Class C (PIG-C) is the first step in GPI pathway and upon its overexpression, Mesothelin (MSLN); an oncogenic GPI-AP, expression is induced. Therefore, blocking GPI pathway is a potential therapy through which multiple pathways can be rectified. Recombinant GPI-CD80 proved to be a potent immunostimulatory protein and currently being evaluated as tumor vaccine. In fact, CD80 is a unique immunomodulator that binds to CD28, CTLA-4 and PD-L1. Furthermore, research advancement showed that non-coding RNAs (ncRNAs) are key epigenetic modulators. Therefore, epigenetic tuning of GPI-APs remains an unexplored area. This study aims at investigating the potential role of ncRNAs in regulating MSLN, PIG-C and CD80 in BC. Potential ncRNAs were filtered by bioinformatics algorithms. MDA-MB-231 cells were transfected with RNA oligonucleotides. Surface CD80 and MSLN were assessed by FACS and immunofluorescence. Gene expression was tested by q-PCR. PIG-C gene was overexpressed in TNBC and its manipulation altered MSLN surface level. Aligning with bioinformatics analysis, miR-2355 manipulated PIG-C and MSLN expression, while miR-455 manipulated CD80 expression. NEAT1 sponged both miRNAs. Paradoxically, NEAT1 lowered PIG-C gene expression while increased MSLN gene expression. This study unravels novel immunotherapeutic targets for TNBC. NEAT1 is potential immunomodulator by sponging several miRNAs. Finally, this study highlights GPI pathway applications, therefore integrating epigenetics, post-translational modifications and immunomodulation.